Método Singapur y las relaciones lógico matemáticas de los niños de preparatoria de la Escuela de Educación Básica Miguel Riofrío de la ciudad de Loja, periodo 2023- 2024. - Rosario Rodríguez, Noelia Estefanía (2024)
The Logical-mathematical relationships play an important role in kids’ life, especially during the beginning of the initial stage, due to that these abilities will be developed in relation with the mathematical concepts, logical reasoning, the comprehension, and the exploration of the environment. The present research aims to determinate if the Singapore methods strengthens the logical-mathematical in kids in high school students of the Miguel Riofrío education school in Loja city, 2023-2024 period. This research was characterized by its quasi-experimental design, using a quantitative approach, with a descriptive scope; therefore, the following methods were applied: inductive-deductive and analytical-synthetic. The sample consisted of 24 children between 5 and 6 years of age. For the diagnosis, the Evamat - 0 battery was applied, evidencing the difficulty presented by the children in developing skills in logical-mathematical relations, observing that 42% were in the low zone in the development of these skills, such complications seem to derive from the inability to relate and apply mathematical concepts in everyday situations, indicating a lack of fundamental understanding of them. To address this problem, an activity guide incorporating the Singapore method was designed and applied, achieving a significant improvement, reducing the percentage of children in the low zone category to 8%. Thus, we can confirm that the Singapore method play a crucial role in kids learning in the logical mathematical relationship, developing the comprehension, the retention, the taste for the application of the mathematics and problem solving of real-life situations through the simple skills, allowing that they build their own knowledge in an active way, absorbing mathematical concepts in natural way. Keywords: Initial stage, skills, abilities, Logical-mathematical, Singapur